2017
DOI: 10.18632/oncotarget.19747
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial calcium uniporter as a target of microRNA-340 and promoter of metastasis via enhancing the Warburg effect

Abstract: BackgroundA shift from oxygen phosphorylation to aerobic glycolysis was known as the Warburg effect and a characteristic of cancer cell metabolism facilitating metastasis. Mitochondrial calcium uniporter (MCU), a key ion channel that mediates Ca2+ uptake into mitochondria, was found to promote cancer progression and metastasis. However, its explicit role in shifting metabolism of breast cancer cells has not been defined.MethodsWe evaluated MCU overexpression or knock-down on migration, invasion and glucose met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…We also demonstrated that transfection of wild type nm23‐H1 complementary DNA (cDNA) into human high‐metastatic large cell lung cancer cells (which exhibit loss of heterozygosity [LOH] of nm23‐H1 ), can regulate the expression of metastatic relative genes and reverse the metastatic phenotype of lung cancer cell lines . Our findings and other reports have provided sufficient evidence to indicate that nm23‐H1 is a metastasis suppressor gene in many tumors . Our studies have also proven that the nm23‐H1 gene is a key and upstream regulative gene in the “lung cancer metastatic suppressive cascade.” However, the exact molecular mechanism by which nm23‐H1 suppresses or reverses lung cancer metastasis is unclear.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…We also demonstrated that transfection of wild type nm23‐H1 complementary DNA (cDNA) into human high‐metastatic large cell lung cancer cells (which exhibit loss of heterozygosity [LOH] of nm23‐H1 ), can regulate the expression of metastatic relative genes and reverse the metastatic phenotype of lung cancer cell lines . Our findings and other reports have provided sufficient evidence to indicate that nm23‐H1 is a metastasis suppressor gene in many tumors . Our studies have also proven that the nm23‐H1 gene is a key and upstream regulative gene in the “lung cancer metastatic suppressive cascade.” However, the exact molecular mechanism by which nm23‐H1 suppresses or reverses lung cancer metastasis is unclear.…”
Section: Introductionsupporting
confidence: 60%
“…[23][24][25][26][27][28][29][30] Our findings and other reports have provided sufficient evidence to indicate that nm23-H1 is a metastasis suppressor gene in many tumors. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Our studies have also proven that the nm23-H1 gene is a key and upstream regulative gene in the "lung cancer metastatic suppressive cascade." [23][24][25][26][27][28][29][30][31][32][33] However, the exact molecular mechanism by which nm23-H1 suppresses or reverses lung cancer metastasis is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain MCU-dependent pro-oncogenic events are thought to be more sensitive to mitoxantrone, such as the increased metastatic abilities of MCF-7 cells and HCC cells, as well as the MCU-dependent chemotherapy resistance in multiple myeloma cells (Arduino et al, 2017;Ren et al, 2017;Song et al, 2013;Yu et al, 2017). Certain MCU-dependent pro-oncogenic events are thought to be more sensitive to mitoxantrone, such as the increased metastatic abilities of MCF-7 cells and HCC cells, as well as the MCU-dependent chemotherapy resistance in multiple myeloma cells (Arduino et al, 2017;Ren et al, 2017;Song et al, 2013;Yu et al, 2017).…”
Section: Pharmacological Inhibitors Of the Mcumentioning
confidence: 99%